Mosquito seasonality and trap type evaluation using routine surveillance data from New Orleans, Louisiana, United States - Nicole A. Scavo; Diana Reyes; Alexandros F. Pavlakis; Claudia Riegel; André B. B. Wilke (PLoS ONE, 2026)
New Orleans, Louisiana, is a major gateway for the introduction of arboviruses into the United States due to high volumes of travel from arbovirus-endemic regions, the influx of migratory birds, and the presence of competent mosquito vectors. To respond to this increasing threat, the New Orleans Mosquito, Termite, and Rodent Control Board conducts routine and response-based mosquito surveillance. Three main types of traps are used in their surveillance system: gravid traps, CDC light traps, and BG-Sentinel traps. Understanding the capability of different trap types in assessing species richness, abundance, and community composition is instrumental in guiding surveillance efforts and responding to travel-associated and locally acquired arboviral infections effectively. This study aims to characterize the temporal dynamics of mosquito vector species in New Orleans, Louisiana, and to evaluate the effectiveness of BG-Sentinel, CDC light, and gravid traps in assessing species richness, abundance, and community composition. Alpha and beta diversity were compared based on trap type. Abundance, Richness, Shannon-Wiener diversity index, and evenness were compared using a Kruskal-Wallis Rank Sum test, followed by a post-hoc Dunn test with Bonferroni correction. Community composition was assessed using pairwise permutational multivariate analysis of variance (perMANOVA) and similarity percentage analysis (SIMPER), both with 10,000 permutations. Significant differences in mosquito abundance and diversity metrics were observed among trap types, indicating that trap choice strongly influences observed mosquito abundance, richness, community composition, and evenness. Gravid and CDC light traps, as well as BG-Sentinel and gravid traps, collected significantly different communities, driven mostly by higher Culex quinquefasciatus abundance in gravid traps. Differences between BG-Sentinel and CDC light traps were primarily driven by Culex salinarius and Aedes vexans , both more frequently collected by CDC light traps. Our results show that trap type significantly influences estimates of species abundance, richness, community composition, and evenness in New Orleans. These findings emphasize the importance of selecting appropriate trap types to generate accurate and actionable surveillance data, essential for guiding and optimizing mosquito control strategies aimed at preventing and responding to arbovirus outbreaks.